Quality of Clean Water Services for Regional Water Companies in Tangerang City - Euis Damayanti; Retnowati WD Tuti (Jurnal Manajemen Pelayanan Publik, 2021)
The Regional Water Supply Company in Tangerang City has an obligation to carry out public service functions and prosper the community. In addition, the location of the settlement is quite far from the Regional Water Supply Company Office, causing less people to become customers. The purpose of this study was to analyze the quality of clean water service in the Tangerang Municipal Water Supply Company. The Analysis Knife used by ServQual (Service Quality) consists of five dimensions, namely Tangible, Reliability, Responsiveness, Assurance and Empathy. The research method used is descriptive with a qualitative approach. Results of the study: Tangibles: available service outlets that make it easier for the community to access Regional Drinking Water Company, and the presence of officers who come directly to the community / Pick up the ball; Responsiveness: there is clear and accurate information, responsive. Reliability: resolve complaints that come from the public quickly. Assurance: providing services ranging from explanations, being polite, adequate employee knowledge and abilities. Empathy: delivery of information to customers that are considered easy to understand and hospitality of employees in responding to complaints that come in.